Stair-climbing interventions on cardio-metabolic outcomes in adults: A scoping review - Anang M. Ghosal, BSc; Baskaran Chandrasekaran, MPT (Journal of Taibah University Medical Sciences, 2024)
الملخص: أهداف البحث: يرتبط الخمول البدني بارتفاع مخاطر الإصابة بالأمراض المزمنة؛ ومع ذلك، فإن جزءا صغيرا فقط من سكان العالم يستوفي التوصيات الخاصة بالنشاط البدني. صعود السلالم هو شكل بسيط وسهل من النشاط البدني الذي ثبت أنه يحسن نتائج القلب والأوعية الدموية لدى البالغين. يستكشف استعراض النطاق الحالي الآثار الفسيولوجية والعلاجية لتدخلات صعود السلالم على عوامل خطر الإصابة بأمراض القلب والأوعية الدموية لدى البالغين. طرق البحث: اتبعت مراجعة النطاق هذه إرشادات الإبلاغ الخاصة بإطار عمل آركسي و أومالي، الذي يجمع الأدلة على مراحل. تم تأطير سؤال البحث على أنه ''ما هي آثار صعود السلالم على نتائج القلب والأوعية الدموية لدى البالغين؟''. تم تحديد المقالات المؤهلة من خلال بحث مكثف في أربع قواعد بيانات إلكترونية، وتم مراجعة وتنظيم بيانات من 24 دراسة بحثية. النتائج: يحسن صعود السلالم القدرة الهوائية (8-33 مل كجم / دقيقة) والمؤشرات الحيوية في الدم بنسبة ≈ 9-15٪. كما أظهرت المراجعة أن ما لا يقل عن 4 - 8 أسابيع من النشاط ضرورية لتغيير مخاطر القلب والأوعية الدموية. يمكن أن يؤدي صعود السلالم المنتظم إلى تحسين مؤشرات مخاطر القلب والتمثيل الغذائي، بما في ذلك تكوين الجسم وضغط الدم ومستويات الكوليسترول وحساسية الأنسولين. لا يزال البحث المتعلق بالتغيرات الالتهابية والعضلية الهيكلية مع نوبات صعود السلالم في مهده. الاستنتاجات: تدخلات صعود السلالم هي شكل من أشكال النشاط البدني بدون تكلفة وسهلة لتحسين مخاطر الإصابة بأمراض القلب والأوعية الدموية لدى البالغين. Abstract: Objective: Physical inactivity is linked with high chronic disease risk; however, only a fraction of the global population meets the recommendations for physical activity. Stair-climbing is a simple and accessible form of physical activity that has been shown to improve cardio-metabolic outcomes in adults. The present scoping review explores the physiological and therapeutic effects of stair-climbing interventions on adult cardio-metabolic disease risk factors. Methods: This scoping review followed the reporting guidelines of the Arksey & O'Malley framework, which collates evidence in stages. The research question was framed as “What are the effects of stair climbing on cardio-metabolic outcomes in adults?”. Eligible articles were identified through an extensive search of four electronic databases, and data from 24 research studies were charted and organized. Results: Stair climbing improves aerobic capacity (8–33 ml kg/min) and serum biomarkers by ≈9–15 %. A minimum of 4–8 weeks are necessary to alter cardiometabolic risk. Regular stair climbing can improve cardio-metabolic risk indicators, including body composition, blood pressure, cholesterol levels, and insulin sensitivity. The research regarding inflammatory and musculoskeletal changes with stair climbing bouts is still in its infancy. Conclusion: Stair climbing interventions are a no-cost and feasible form of physical activity for improving cardiometabolic disease risk in adults.